1990
DOI: 10.1159/000153915
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Linkage between Chromosome 5 Markers and Schizophrenia

Abstract: Linkage between chromosome 5 markers and schizophrenia has been proposed for a small number of Icelandic and English families. Three subsequent reports have failed to replicate this report. To increase the number of tested kindreds, we collected seven North American families with schizophrenia and genotyped them at 4 loci that span the region 5p13–5q11–14, including the two markers used in the single positive linkage report. The data were analyzed with models of affection status similar to those utilized in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…32 Initial positive linkage findings 10 were not replicated. 33 In another report, a patient with schizophrenia, dysmorphic features, moderate learning disability and an interstitial deletion at 5q22 was described. 34 Two schizophrenia linkage studies 35,36 suggest involvement in the region 5q22-31.…”
Section: Chromosome 5qmentioning
confidence: 98%
“…32 Initial positive linkage findings 10 were not replicated. 33 In another report, a patient with schizophrenia, dysmorphic features, moderate learning disability and an interstitial deletion at 5q22 was described. 34 Two schizophrenia linkage studies 35,36 suggest involvement in the region 5q22-31.…”
Section: Chromosome 5qmentioning
confidence: 98%
“…Numerous replication studies failed to support for this finding [Aschauer et al, 1990] and a combined reanalysis of published data effectively ruled out straightforward linkage heterogeneity [Kennedy et al, 1988 al., 1990; Crowe et al, 1991;Campion et al, 1992;Macciardi et al, 1992]. Recently, however, there has been renewed interest in chromosome 5, although in two separate locations, one close to, and the other distant from, that reported by Sherrington et al These are shown in Figure 5.…”
Section: Chromosomementioning
confidence: 99%
“…The disadvantage of our small sample size is outweighted by it being a homogenous ethnic and diagnostic population from a small defined region in eastern part of Austria, recruited by scientists experienced in linkage studies [27][28][29].…”
Section: Introductionmentioning
confidence: 99%